2016
DOI: 10.3389/fphys.2016.00601
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Adjustments and Circulating MicroRNA Reprogramming Are Involved in Early Acclimatization to High Altitude in Chinese Han Males

Abstract: Background: Altitude acclimatization is a physiological process that restores oxygen delivery to the tissues and promotes oxygen use under high altitude hypoxia. High altitude sickness occurs in individuals without acclimatization. Unraveling the molecular underpinnings of altitude acclimatization could help understand the beneficial body responses to high altitude hypoxia as well as the altered biological events in un-acclimatized individuals. This study assessed physiological adjustments and circulating micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…The above two studies focused on the miRNAs of native highaltitude acclimatized populations, and both plasma and RBC miRNA profiles revealed RBC-specific functionality, emphasizing the importance of tightly regulating miRNAs during hypoxic exposures. However, it is interesting to note that miRNAs have also been implicated in facilitating the acclimatization process and the restoration of oxygen delivery to tissues for individuals at high altitudes (Liu et al, 2016). The physiological adjustments observed during acclimatizationincluding those affecting hematology, stress hormones and lipid moleculeswere found to be strongly correlated with hypoxia-mediated regulation of circulating miRNAs (Liu et al, 2016), where 86 miRNAs (79 up-regulated and seven down-regulated) were significantly differentially expressed upon exposure to hypoxia.…”
Section: Applicability Of Blood Mirnamentioning
confidence: 99%
See 2 more Smart Citations
“…The above two studies focused on the miRNAs of native highaltitude acclimatized populations, and both plasma and RBC miRNA profiles revealed RBC-specific functionality, emphasizing the importance of tightly regulating miRNAs during hypoxic exposures. However, it is interesting to note that miRNAs have also been implicated in facilitating the acclimatization process and the restoration of oxygen delivery to tissues for individuals at high altitudes (Liu et al, 2016). The physiological adjustments observed during acclimatizationincluding those affecting hematology, stress hormones and lipid moleculeswere found to be strongly correlated with hypoxia-mediated regulation of circulating miRNAs (Liu et al, 2016), where 86 miRNAs (79 up-regulated and seven down-regulated) were significantly differentially expressed upon exposure to hypoxia.…”
Section: Applicability Of Blood Mirnamentioning
confidence: 99%
“…However, it is interesting to note that miRNAs have also been implicated in facilitating the acclimatization process and the restoration of oxygen delivery to tissues for individuals at high altitudes (Liu et al, 2016). The physiological adjustments observed during acclimatizationincluding those affecting hematology, stress hormones and lipid moleculeswere found to be strongly correlated with hypoxia-mediated regulation of circulating miRNAs (Liu et al, 2016), where 86 miRNAs (79 up-regulated and seven down-regulated) were significantly differentially expressed upon exposure to hypoxia. Key functional targets of these circulating miRNAs include low-density lipoprotein-cholesterol, cholesterol metabolism and cortisol synthesis.…”
Section: Applicability Of Blood Mirnamentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies regarding the pathophysiological etiology of HAH have suggested that HAH can be induced by hypobaric hypoxia causing overperfusion of the microvascular beds, brain swelling, activation of the trigeminal vascular system, and sensitization of intracranial pain receptors (Burtscher et al, 2011 ). Furthermore, the known independent risk factors for HAH include increased heart rate (HR), posterior cerebral circulation, vertebral artery diastolic velocity, and anxiety; decreased pulse oxygen saturation (SpO 2 ) and vigor; and a history of migraine or microRNA dysregulation (Silber et al, 2003 ; Lawley, 2011 ; Alizadeh et al, 2012 ; Bian et al, 2013 , 2015 ; Liu et al, 2016 ; Dong et al, 2017 ; Guo et al, 2017 ). However, the actual underlying mechanisms, clinical manifestations and risk factors/predictors remain not entirely clear, despite accumulating evidence regarding HAH (Marmura and Hernandez, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Replicated microRNAs were averaged, and probes with intensities ≥30 in all samples were selected for normalization. Detailed instructions were as previously described (Liu et al, 2016 ). After normalization, significantly differentially expressed microRNAs between the two groups were identified using Fold change and P -value cutoffs of 2 and 0.05, respectively.…”
Section: Methodsmentioning
confidence: 99%